EKSISTENSI OTORITAS JASA KEUANGAN SEBAGAI LEMBAGA NEGARA INDEPENDEN (STUDI KASUS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 25/PUU-XII/2014) - Isharyanto, Isharyanto; Laxamana, M.R.F. Izzata (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
The state of Indonesia is a country that adheres to the principle of Pancasila. The principle of Pancasila is a concept that focuses more on mutual cooperation or kinship. Reflected through the sound of the Pancasila Five Precepts is “Social Justice for all Indonesian people.” In the DECISION OF THE CONSTITUTIONAL COURT OF THE NUMBER 25 / PUU-XII / 2014, several articles of both parties have been enacted on the article of OJK itself, and then there are several arguments or considerations which are included in the Constitutional Court itself. The legal consequences of the Constitutional Court Decision Number 25 / PUU-XII / 2014 are the amendments to article 1 number 1 of the OJK Law, namely the abolition of the word “free from the interference of other parties”, and let the word stand alone. Article 1 Sub-Article 1 of the OJK Law meanjadi “Financial Services Authority, hereinafter abbreviated OJK, is an independent institution, which has the functions, duties, and authority of regulation, supervision, examination and investigation in this law.”